Bile Acids and Their Value for Central Nervous System - Yu. O. Shulpekova; P. E. Tkachenko; E. N. Shirokova; I. V. Damulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A review to highlight the bile acids importance as steroid mediators of nervous system activity and show the nervous system involvement in cholesterol metabolism and bile acids production.Key points. Presence of bile acid membrane and nuclear receptors and their activation role in mediating manifold metabolic processes have been established in various organs and tissues. Bile acid transporters are discovered in CNS. The animal brain under physiological conditions was found to contain about 20 bile acid types of likely innate origin suggested by their high contents; the bile acids spectrum in CNS differs significantly from blood plasma. Clinical and experimental works are conclusive about the CNS bile acids influence on mitochondrial membrane, their antioxidative role and, probably, steroid-mediator involvement in indirect regulation of memory, attention, motor functions and appetite.Conclusion. Bile acids act as pleiotropic signalling molecules affecting various tissues. The presence in CNS of various bile acid synthesis-related receptors and enzymes indicates their value in brain functioning and warrants research into their metabolism.